2021
DOI: 10.7150/jca.58824
|View full text |Cite
|
Sign up to set email alerts
|

NEAT1/miR-101-dependent Up-regulation of DNA-PKcs Enhances Malignant Behaviors of Pancreatic Ductal Adenocarcinoma Cells

Abstract: Background: Although we previously revealed that DNA-dependent protein kinase catalytic subunit (DNA-PKcs) is overexpressed in pancreatic ductal adenocarcinoma (PDAC) and important for gemcitabine resistance, the role of DNA-PKcs in the progression and metastasis of PDAC remain unclear. To date, the upstream signaling events stimulating DNA-PKcs overexpression in PDAC are still not well characterized. Methods: Expression of DNA-PKcs was measured by western blot. The levels of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 34 publications
(62 reference statements)
0
4
0
Order By: Relevance
“…The contribution of NEAT1 to cancer progression has also been studied in other cancers, including cervical cancer [ 77 ], cholangiocarcinoma [ 78 ], endometrial cancer [ 79 ], esophageal carcinoma [ 80 ], gallbladder cancer [ 81 ], glioblastoma [ 82 ], Hodgkin’s lymphoma [ 83 ], laryngeal carcinoma [ 84 ], melanoma [ 85 ], multiple myeloma [ 11 ], nasopharyngeal carcinoma [ 86 ], osteosarcoma [ 87 ], pancreatic carcinoma [ 88 ], retinoblastoma [ 89 ], thyroid cancer [ 90 ], and tongue carcinoma [ 91 ]. In those cancers, NEAT1 plays a pro-proliferative role and promotes the progression of cancer by upregulating the expression of some oncogenes or downregulating the expression of some tumor suppressor genes.…”
Section: Neat1 Sponges Micrornas and Stabilizes Mrnasmentioning
confidence: 99%
“…The contribution of NEAT1 to cancer progression has also been studied in other cancers, including cervical cancer [ 77 ], cholangiocarcinoma [ 78 ], endometrial cancer [ 79 ], esophageal carcinoma [ 80 ], gallbladder cancer [ 81 ], glioblastoma [ 82 ], Hodgkin’s lymphoma [ 83 ], laryngeal carcinoma [ 84 ], melanoma [ 85 ], multiple myeloma [ 11 ], nasopharyngeal carcinoma [ 86 ], osteosarcoma [ 87 ], pancreatic carcinoma [ 88 ], retinoblastoma [ 89 ], thyroid cancer [ 90 ], and tongue carcinoma [ 91 ]. In those cancers, NEAT1 plays a pro-proliferative role and promotes the progression of cancer by upregulating the expression of some oncogenes or downregulating the expression of some tumor suppressor genes.…”
Section: Neat1 Sponges Micrornas and Stabilizes Mrnasmentioning
confidence: 99%
“…In addition, it is well known that lncRNA NEAT1 acts as a ceRNA of miRNA to inhibit miRNA expression, eventually leading to the elevated expression of target gene [ 27 ]. The current study also exhibited that lncRNA NEAT1 could competitively bind to miR-491-5p to induce PCa cell proliferation, migration, and gemcitabine resistance.…”
Section: Discussionmentioning
confidence: 99%
“…NEAT1 is a transcriptional mediator for multiple genes implicated in pancreatic carcinogenesis [ 26 ] via a competing endogenous RNA (ceRNA) mechanism interacting with miRNAs. Prior findings have suggested that NEAT1/miR-101-dependent release of DNA-PKcs augments the malignant behaviors of pancreatic ductal adenocarcinoma cells [ 27 ]. Whereas, how the effect of NEAT1 was delivered to cancer cells remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“… 14 LncRNA serves as a competitive endogenous RNA (ceRNA) of a specific miRNA and inhibits the expression of this target miRNA. 15 , 16 The evidence can be clearly seen in the publication of Perez-Hernandez et al, which enumerates that miR-146a is relative to albuminuria in patients with EH. 17 Luo et al illustrate this view evidently by the documentation that the expression of miR-10a-5p and miR-497-5p is lessened in 98 patients with EH.…”
Section: Introductionmentioning
confidence: 98%